2006
DOI: 10.1093/ps/85.8.1449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feed Restriction and Realimentation on Digestive and Immune Function in the Leghorn Chick

Abstract: How regulatory changes of digestive and immune functions of the gut influence each other has not been sufficiently studied. We tested for simultaneous changes in the digestive physiology and mucosal immune function of the guts of White Leghorn cockerel chicks undergoing food restriction and realimentation. Chicks were assigned to 1 of 3 groups: control = fed ad libitum 7 to 17 d of age; restricted = feed restricted d 12 to 17 (at 2 restriction levels: 54 and 34% ad libitum); refed = feed restricted d 7 to 13 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…Our findings regarding maltase activity are supported by Fassbinder-Orth and Karasov (2006), in which the jejunal and ileal maltase activities of young animals were not Duarte et al: Feed Restriction affected by feed restriction. Maltase activity results were also correlated with the response of mRNA expression previously observed in our laboratory (Duarte et al, 2011), which suggests that this gene can have a pre-transcriptional regulation (Gal-Garber et al, 2000).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings regarding maltase activity are supported by Fassbinder-Orth and Karasov (2006), in which the jejunal and ileal maltase activities of young animals were not Duarte et al: Feed Restriction affected by feed restriction. Maltase activity results were also correlated with the response of mRNA expression previously observed in our laboratory (Duarte et al, 2011), which suggests that this gene can have a pre-transcriptional regulation (Gal-Garber et al, 2000).…”
Section: Discussionsupporting
confidence: 83%
“…Although there are discrepancies in the literature concerning the effects of feed restriction on the gastrointestinal system, the observed reduction in organ weights at both ages is an expected response given the trophic effects of nutrients (Fassbinder-Orth and Karasov 2006;Wijtten et al, 2010) and the reduction in the basal metabolic rate in response to feed restriction (Christensen et al, 2012). A decrease in metabolic rate could lead to a reduction in the energy required to maintain gastrointestinal turnover.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, these birds can maintain their growth rate during meal feeding. Changes in the enzymatic or absorptive capacity of the gastrointestinal tract or changes in post-absorptive processes can change feed efficiency (Fassbinder-Orth & Karasov 2006). The improvement in feed efficiency observed in feed-restricted chickens was probably attributed to reduced overall maintenance requirements, improvement of chemical digestion and nutrient absorption in the broiler gut (Pinheiro et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, the high growth under ad libitum feeding is occasionally associated with increasing mortality and severe leg problems. Feed restriction in poultry has been commonly used to control the body weight (Fassbinder-Orth & Karasov 2006) and alleviate metabolic disorders such as ascites (Özkan et al 2006) and leg problems (Wijtten et al 2010, Saffar & Khajali 2010. Also the effect of feed restriction on lipid metabolism was documented in studies of some research groups (Lippens et al 2009, Yang et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Fassbinder-Orth & Karasov (2006) also reported that the direction of nutrients for the growth of source organs such as small intestine gets priority over sink organs such as lean and fat. None of the other visceral organ weights and fat percentage were significantly affected by the diets.…”
Section: Carcass Parameters and Meat Organoleptic Propertiesmentioning
confidence: 99%